1996
DOI: 10.1006/dbio.1996.9988
|View full text |Cite
|
Sign up to set email alerts
|

PDGF-A Is Required for Normal Murine Cardiovascular Development

Abstract: Several lines of evidence suggest that platelet-derived growth factor A chain (PDGF-A) is required for normal embryonic cardiovascular development. To test this directly, we introduced anti-PDGF-A neutralizing antibodies into mouse deciduas in utero at Embryonic Days (E) 8.5, 9.5, and 10.5. This resulted in the selective disruption of PDGF-A ligand-receptor interactions in vivo for a period of 18-24 hr and allowed us to assess both if PDGF-A is required for cardiovascular development and when it is required. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Moreover, the PDGFR␣ is also regulated in angiogenesis (29), and suggested that the PDGF AB-␣ receptor communication pathway may be involved in the regulation of gene(s) critical to cardiac vascular development. Previous reports have described the importance of PDGF A and B, and PDGFR␣ in the cardiac vasculature (7)(8)(9)(10)(11)(12). PDGF ␤ receptor knockout mice have no cardiac pathology (13), but they have increases in PDGFR␣, which may result in an underestimation of the role of the ␤ receptor in the cardiac vascular PDGF communication (13).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the PDGFR␣ is also regulated in angiogenesis (29), and suggested that the PDGF AB-␣ receptor communication pathway may be involved in the regulation of gene(s) critical to cardiac vascular development. Previous reports have described the importance of PDGF A and B, and PDGFR␣ in the cardiac vasculature (7)(8)(9)(10)(11)(12). PDGF ␤ receptor knockout mice have no cardiac pathology (13), but they have increases in PDGFR␣, which may result in an underestimation of the role of the ␤ receptor in the cardiac vascular PDGF communication (13).…”
Section: Discussionmentioning
confidence: 99%
“…24,25 In adult SMCs, these PDGF isoforms generally induce a more synthetic phenotype. For example, PDGF-B downregulates α-SMA expression in rat aortic SMCs.…”
Section: Biochemical Factorsmentioning
confidence: 99%
“…Transcription of the A-chain gene is activated rapidly by a wide range of growth factors, cytokines and other mitogens (5-7), whereas complex cell type-specific patterns of A-chain transcription appear to underlie the regulation of cell proliferation during embryogenesis (8) and cellular differentiation (9). A-chain null mice exhibit abnormalities in early embryonic development and formation of lung alveolar myofibroblasts (10, 11), whereas expression of the A-chain and the PDGF ␣-receptor also appear to critical for development of the cardiovascular and nervous systems in mice (12)(13)(14). PDGF also appears to be critical for placental development, with high expression of A-chain observed in multiple cell types of the placenta including trophoblasts (2, 15), as well as extraembryonic membranes and uterine smooth muscle cells during pregnancy (15, 16).…”
Section: Platelet-derived Growth Factor (Pdgf)mentioning
confidence: 99%